Forgiveness, Gratitude, Happiness, and Prosocial Bystander Behavior in Bullying - García-Vázquez, Fernanda Inéz; Valdés-Cuervo, Angel Alberto; Martínez-Ferrer, Belén; Parra-Pérez, Lizeth Guadalupe (Frontiers in Psychology, 2020)
The relationships among character strengths (forgiveness and gratitude), happiness, and pro-social bystander behavior in bullying were analyzed. The sample includes 500 (early adolescents) and 500 (middle adolescents) of both genders, between 12 and 18 years old (M age = 14.70, SD = 1.58). Two structural equation models were calculated. Results of the first model indicated that forgiveness, gratitude, and happiness had a direct positive relation with pro-social bystander behavior. Furthermore, human strengths were indirectly related to prosocial behavior in bullying for this effect in happiness. The second model showed that pro-social bystander behavior had a positive effect on human strengths and happiness. Multi-group analyses indicated that gender and stage of adolescence did not moderate the relations found in the model. Overall findings suggest a reciprocal relationship between character strengths, happiness, and pro-social bystander behavior.